Who is lying and who is telling the truth? The role of education in the development of understanding of lies - Šimonji Gabrijela; Major Lenke (Nastava i Vaspitanje)
Lying is a common phenomenon that becomes a part of human life from a certain point in individual development. In many cases, it is through poorly chosen educational methods that children learn to lie. When family or school education is based on the principle of punishment, children quickly learn that lying can help them avoid consequences. At the same time, lying is a socially unacceptable behavior. Children acquire socially acceptable behaviors as they develop their social competencies. For children, what is good and bad does not necessarily align with what society deems acceptable. Our research question focuses on whether adolescent children view lying in the same way as adults or if they perceive various lying situations and elements differently. In our study, we replicated Coleman and Kay's experiment on lying using their measurement tool adapted to the Hungarian language. The study was conducted among upper primary school students who are native Hungarian speakers in Serbia. The results show that children differ from adults in their perception of lying and their evaluation of the complex elements that constitute lies. Our research findings highlight the crucial role that schools and appropriately chosen educational methods can play in shaping a proper moral value system, particularly in developing social competencies.